Dynamics and cytochemistry of oogenesis in Astyanax fasciatus (Cuvier) (Teleostei, Characiformes, Characidae) from Rio Sapucaí, Minas Gerais State, Brazil - Garcia, José Antônio Dias; Chini, Helena A.S.; Maistro, Edson Luis [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Oogenesis involves a set of transformations which are undergone by female germ cells These cells change into oogonias and then into mature oocytes. Sexually mature female fish were collected monthly, during one year, from the Sapucaí River, a tributary of the Rio Grande, which is part of the Furnas Reservoir in the state of Minas Gerais. During the several stages of maturation, we observed small round oogonias with a large nucleus, a single nucleolus, and weakly stained cytoplasm with eosinophilic granules. The primary oocytes showed a large basophilic nucleus, with a developed peripheral nucleolus and a reduced cytoplasm. The previtellogenic oocytes presented voluminous cytoplasm and nucleus with several small peripheral nucleoli. The oocytes underwent vitellogenesis with the development of the zona radiata and the follicle cells. Their cytochemical reactions indicated that the two layers of the zona radiata of A. fasciatus contained proteins and polysaccharides. The initially squamous follicle cells, became cuboidal. In mature oocytes, the nucleus moved toward the periphery, next to the micropyle, and the yolk granules formed by proteins, fulfilled the cytoplasm. The clear unstained vesicles are likely to be the cortical alveoli in the perivitelline region.
Keywords: Teleostei; Characidae; Astyanax fasciatus; oogenesis; cytochemical